2017
DOI: 10.7307/ptt.v29i2.2101
|View full text |Cite
|
Sign up to set email alerts
|

The Crossing Speed of Elderly Pedestrians

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In addition, with reference to relevant research, it is recommended that the proportion of the elderly exceeds 15%, and for every 10% increase, the value of the crossing speed is reduced by 0.1 m/s [12]. The speed value researched in the paper is the same as the Knoblauch [7] results, but lower than the values given in HCM and by Coffin et al [4,8,10,13], and higher than the values given by Diaz and Trpkovic [12,14]. About the elderly pedestrian ratio that setting the speed is lower than the 20% provided by the researchers [10,13,15].…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…In addition, with reference to relevant research, it is recommended that the proportion of the elderly exceeds 15%, and for every 10% increase, the value of the crossing speed is reduced by 0.1 m/s [12]. The speed value researched in the paper is the same as the Knoblauch [7] results, but lower than the values given in HCM and by Coffin et al [4,8,10,13], and higher than the values given by Diaz and Trpkovic [12,14]. About the elderly pedestrian ratio that setting the speed is lower than the 20% provided by the researchers [10,13,15].…”
Section: Resultsmentioning
confidence: 63%
“…In HCM2000 [13], it is recommended that the proportion of the elderly in the area below 20% adopts 1.22 m/s as the design speed, and in the area where the proportion of the elderly exceeds 20%, the design speed is 1.00 m/s, and if the proportion of the elderly increases by 10%, the pedestrian walking design speed is reduced by 0.1 m/s. Trpkovic et al [14] investigated the walking speed of the elderly pedestrians at ten intersections, and the 15 th percentile walking speed was 0.88 m/s. For the relationship between the proportion of the elderly pedestrians and the pedestrian crossing speed value, Milazzo et al found the 15 th percentile walking speed when reduced by at least 0.05 from the recommended value was taken as the design speed of the elderly pedestrian crossing street, and the elderly pedestrian threshold was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Crossing behavior. Walking speed is not the only reason that crossing at a signalized or designated crossing place can be dangerous; the way in which pedestrians adhere to and understand crossing rules can also inform safety (see Table 4 for a summary of papers; please note two of the papers in this section, Coffin &Morrall, 1995 andTrpković et al, 2017, are described in Table 2).…”
Section: Crossing At Signalized Crossingsmentioning
confidence: 99%
“…Among them, present studies can be divided into internal human factors and external environment by the differences in the purpose of the investigation. The internal human factors mainly consider the effects of age [ 3 ], gender [ 4 ], gap acceptance [ 5 , 6 ], mental effects [ 7 ], and crossing behavior selection as an individual or group of pedestrians [ 6 ]. External environment factors include built environment features [ 8 ], traffic conditions [ 9 ], the length of red-light time [ 10 ], time of the trip [ 11 ], social characteristics [ 12 ], and road crosswalk facilities [ 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%